Recovery of Physical Activity After Cesarean Delivery and Its Relationship With Pain. Issue 3 (September 2020) - Sharpe, E.E.; Booth, J.L.; Houle, T.T.; Pan, P.H.; Harris, L.C.; Aschenbrenner, C.A.; Eisenach, J.C.
Abstract : ( Pain . 2019;160:2350–2357) While all patients experience pain when recovering from a major surgery, not much is known about the day-to-day recovery from pain and inactivity that surgical patients experience. Previous research has attempted to quantify postoperative activity and pain levels, but these studies do not employ a practical approach to data collection that is both consistent and adequately detailed. The goals of this study were 4-fold: (1) characterize a feasible approach to recording exercise and pain for postoperative patients, (2) determine the connection between daily pain and levels of activity or inactivity, (3) determine the form of recovery of activity, and (4) explore factors that influence physical activity and determine if they could predict recovery time.